Analisis Kualitas Instrumen Tes Hasil Belajar IPAS Materi Wujud Zat dan Perubahannya - Surya, Adi Darma; Sumarno, Sumarno; Muhtarom, Muhtarom (FONDATIA, 2023)
The instruments used to measure student learning outcomes, especially in science learning at the elementary school level, are required to be of good quality and have been tested. This study aims to determine the quality of the science achievement test instrument for class IV SD, especially in the matter of matter and its changes based on content validity, reliability, discriminating power and level of difficulty of the test. The subjects of this study were lecturers, class teachers and fourth grade elementary school students. The approach used in this research is descriptive quantitative. Quantitative data analysis techniques were used to determine the quality level of the instrument based on empirical data while qualitative data were used to determine the category level of validity, reliability, discriminatory power and level of test difficulty. The results showed that the quality of the 30-item 100% validity of the test instrument for elementary science class IV material form of matter and its changes with a reliability of 0.901 (very good category). Based on the differentiating power test, there are 1 item in the Very Good category, 16 items in the moderate category, 13 items in the good category. Meanwhile, based on the difficulty index of the test, there are 2 items in the easy category, 27 items in the moderate category, and only 1 item in the difficult category. Thus, overall the test instrument has good quality and is feasible and can be used to measure students' learning outcomes in science learning on material form of matter and its changes